Massive Myocardial Staining and Thebesian Venous Opacification during Complicated Coronary Angiography - Ucar, Fatih Mehmet; Ozeke, Ozcan; Duman, Ilker; Canpolat, Ugur; Kisacik, Halil Lutfi (International Journal of Angiology, 2016)
Myocardial staining is a complication of coronary angiography or intervention procedures and consists of extravasations of contrast material into the myocardium. The powerful injection of contrast (myocardial staining) is caused by the improper positioning of the angiography or guiding catheter and can lead to refractory ventricular tachyarrhythmias and occasionally cardiac death. It results in small puffs of dye extravasating into pericoronary space (epicardial or myocardial).We presented an interesting image of a massive myocardial staining and dense coronary and thebesian venous opacification during complicated right coronary angiography. This case illustrates the value of careful manipulation and positioning of the coronary catheter during coronary angiogram.
Keywords: myocardial staining; coronary angiography; complication